The Effectiveness of Animated Video Towards Students' Ability in Writing Narrative Text at SMKN 1 Rejotangan: Pengaruh Video Animasi Terhadap Kemampuan Siswa dalam Menulis Teks Naratif - Tasya Azzahra; Willy Anugrah Gumilang (STKIP PGRI Trenggalek, 2022)
This study was aimed to know students ability in writing narrative if there is significant different before and after being taught using animated video on second grade students at SMKN 1 Rejotangan. This study was quantitative approach pre-experimental research. During the research, researcher collected data by giving pre-test, activities in experiment, and post-test. The data was an essay writing. In the first meeting students was given pretest to measure their ability in writing before being taught with animated video. Then, researcher give posttest after taught using animated video. Due to pandemic of Covid-19, Researcher did the experiment by online through zoom meeting and google form. Some problem that faced by the students in writing is hard to find ideas to write. Animated video as teaching and learning media, it can help students to get ideas after watching the animated video. The mean score of pre-test was 11.43 and the mean score of post-test was 16.86. The significant different of both scores indicated that the method is effective to improve students skill in writing narrative. The conclusion from the research is animated video can be used as media to help students writing better and succeeded teaching and learning process.